Handbook of research on computational forensics, digital crime, and investigation : methods and solutions - Li, Chang-Tsun , 1914- (Gale virtual reference library, 2010)
"This book provides a media for advancing research and the development of theory and practice of digital crime prevention and forensics, embracing a broad range of digital crime and forensics disciplines" -- Provided by publisher